Storage and encryption file authentication for cloud-based data retrieval - Mustafa Qahtan Alsudani; Hassan Falah Fakhruldeen; Heba Abdul-Jaleel Al-Asady; Feryal Ibrahim Jabbar (Institute of Advanced Engineering and Science, 2022)
The amount of data that must be processed, stored, and modified rises as time passes. An enormous volume of data from a wide range of sources must be stored on a safe platform. Maintaining such a large volume of data on a single computer or hard drive is impracticable. As a result, the cloud is the ideal platform for storing any quantity of data. An advantage of storing data in the cloud is that it may be accessed at any time and from any device. However, the security of data stored in the cloud is a big concern. Because of this, despite the benefits, most users are reluctant to move their papers to the cloud. The data should be encrypted before sending it off to the cloud service provider to avoid this issue. It's a great way to increase the security of your papers. According to a new technique presented in the system, data may be searched across encrypted files without compromising the privacy and security of various data owners. Implementing the pallier homomorphic encryption method makes it possible to perform computations on encrypted data without decryption.